Dissociated Glycemic Status in Diabetes Mellitus: A Meta-Analysis of the Interaction between Acute Stress Hyperglycemia and Chronic Glycemic Control on Sepsis Outcomes - Novia Wira Tungadi (Phlox Institute: Indonesian Medical Research Organization, 2026)
Introduction: Sepsis profoundly complicates diabetes mellitus, yielding disproportionately high mortality. Clinicians traditionally utilize absolute admission blood glucose for risk stratification. However, this metric is fundamentally flawed in pre-existing diabetes because chronic hyperglycemia alters the physiological baseline. The concept of dissociated glycemic status—quantified as the stress hyperglycemia ratio or glycemic gap—captures the discordance between acute stress hyperglycemia and chronic Hemoglobin A1c. This study investigated whether dissociated status serves as a superior predictor of sepsis mortality compared to absolute hyperglycemia, with a specific subgroup focus on the distinct pathophysiology of Type 1 Diabetes. Methods: A systematic review and meta-analysis of eight manuscripts, including registry data, clinical cohorts, and pre-clinical models was conducted. The human incidence cohort encompassed over 300,000 subjects; the mortality analysis included approximately 3,500 patients. The primary exposure was dissociated glycemic status. The primary outcome was sepsis-related mortality. Animal model data and glycemic variability metrics were strictly segregated from the primary quantitative synthesis. Data were synthesized using a random-effects model, assessing heterogeneity via the I-squared statistic, alongside a comprehensive risk of bias assessment. Results: Absolute hyperglycemia failed to independently predict mortality when adjusted for chronic control. A high dissociated glycemic status is strongly associated with mortality (Pooled Odds Ratio 2.14; 95 % Confidence Interval 1.65 to 2.78; I2 42 percent). Separate analysis demonstrated that glycemic variability independently increased mortality risk. Type 1 Diabetes patients exhibited a 3.7-fold increase in sepsis hospitalization compared to controls. Review of pre-clinical models suggested this vulnerability in Type 1 Diabetes is driven by an immunoparalysis phenotype rather than a classic cytokine storm. Conclusion: The interaction between acute and chronic glycemia dictates survival in diabetic sepsis. Dissociated glycemic status represents a critical vital sign indicating a failure of metabolic and immune homeostasis.